Current Status and Future Earth System Studies in Northern Eurasia: Northern Eurasia Earth Science Partnership Initiative (NEESPI) Conference and Workshop; Petrozavodsk, Russia, 1–5 September 2013. (24th December 2013) - Groisman, Pavel; Gordov, Evgeny; Maksyutov, Shamil
Abstract : Northern Eurasia is a sensitive and rapidly changing area with the signal of climate change effects already observed in many components of the Earth's system. The ongoing warming in the Northern Eurasia Earth Science Partnership Initiative (NEESPI) domain was substantially larger than for the globe and during the past 50 years, with a rate of the annual temperature increase of 0.33°C per decade. In addition, this region experienced impacts of abrupt institutional and economic changes in the former Soviet Union countries, east Europe, Mongolia, and China.